The Influence of Profit Persistence, Capital Structure, and Dividend Policy on Earnings Quality - Brilian, Britania Reskin; Effriyanti, Effriyanti (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
This research is motivated by the fact that currently profit is very important for investors and other users of financial reports to understand. Quality profits can be used to make the right decisions, therefore profits are still very important to discuss. This study aims to analyze the effect of profit persistence, capital structure, and dividend policy on earnings quality. This type of research is quantitative research with secondary data sources. The population in this study is 75 energy sector companies listed on the Indonesia Stock Exchange in 2018-2022. The sample selection method used in this study is purposive sampling so that the final sample obtained by this method is 14 companies with 5 years of research obtained 70 data. The research results show that simultaneously the variables of profit persistence, capital structure and dividend policy have an effect on earnings quality. Then, partially, the earnings persistence and capital structure variables have no effect on earnings quality. Meanwhile, the dividend policy variable influences earnings quality. Based on the research results, it can be concluded that companies that have increasingly consistent profits and companies that use funds originating from debt will not influence the high or low quality of the profits produced by the company, while companies that have a higher dividend policy will have a higher quality of profits produced by the company.